Trends and Gradients in Top Tax Elasticities: Cross-Country Evidence, 1900 2014 - Enrico Rubolino; Daniel Waldenström (Institute of Labor Economics (IZA), 2017)
We compile data spanning the period 1900 2014 and up to 30 countries to study long-run patterns in the tax elasticity of top incomes. Our results show that top tax elasticities vary tremendously over time; they were medium-to-low before 1950, virtually zero during the postwar era up to 1980 and have thereafter increased to unprecedented levels. We document a strong income gradient in tax response within the top, underlining the importance to study even small top groups separately. Several mechanisms are investigated. Tax-driven income shifting between wage and capital income is important in the very top. Wars, financial crises, and country-specific effects and trends have bearing on top elasticities whereas standard macroeconomic factors and indicators of "real responses" do not.
Keywords: D31; H21; H24; H26; N40; 330; taxation; income inequality; economic history